The Effect of Reverse Engineering Applications on_x000D_ Academic Achievement and Problem Solving Skills of_x000D_ Secondary School Students - (:unkn) unknown (My University, 2020)
The purpose of this study is to investigate the effect of reverse engineering applications on academicachievement and problem solving skills in 8th grade students. The sample of the study consisted of a total of 56students, 28 of whom were experimental and 28 of which were control group in a public school in Eyyübiye districtof Şanlıurfa province in 2018-2019 academic year. In the control group, the courses were taught with theconstructivist approach methods and techniques proposed by the program, while in the experimental group, reverseengineering applications were added along with the methods and techniques suggested by the program. Researchfrom quantitative research approach; A total of 60 questions prepared by Taşçı (2018) were collected by ScienceAcademic Achievement Test and Problem Solving Inventory developed by Serin, Serin and Saygılı (2010). Inorder to compare the effectiveness of reverse engineering applications, the tests were applied to the experimentaland control group students as pre- and post-tests and the scores between the groups were compared. In the study;It is concluded that reverse engineering applications supported education is more effective than constructivistteaching in improving the academic achievement and problem solving skills of 8th grade students.

Bu araştırmanın amacı tersine mühendislik uygulamalarının 8. sınıf öğrencilerinde akademik başarılarına_x000D_ ve problem çözme becerilerine etkisinin incelenmesidir. Çalışmanın örneklemini 2018-2019 eğitim öğretim_x000D_ yılında Şanlıurfa ili Eyyübiye ilçesinde yer alan bir devlet okulunda 8. sınıfta öğrenim gören 28’i deney, 28’i_x000D_ kontrol grubu olmak üzere toplam 56 öğrenciden oluşturmaktadır. Kontrol grubunda dersler programın önerdiği_x000D_ yapılandırmacı yaklaşım yöntem ve teknikleriyle işlenirken, deney grubunda programın önerdiği yöntem ve_x000D_ tekniklerin yanında tersine mühendislik uygulamaları eklenerek işlenmiştir. Araştırma nicel araştırma_x000D_ yaklaşımından; Taşçı (2018) tarafından hazırlanan toplam 60 soruluk Fen Bilimleri Akademik Başarı Testi ve_x000D_ Serin, Serin ve Saygılı (2010) tarafından geliştirilen Çocuklar İçin Problem Çözme Envanteri ile toplanmıştır._x000D_ Tersine mühendislik uygulamalarının etkililiğini karşılaştırmak amacıyla deney ve kontrol grubu öğrencilerine_x000D_ ilgili testler ön ve son test olarak uygulanmış olup gruplar arası puanlar karşılaştırılmıştır. Araştırmada; tersine_x000D_ mühendislik uygulamaları destekli eğitimin 8. sınıf öğrencilerinde akademik başarılarını ve problem çözme_x000D_ becerilerini geliştirmede yapılandırıcı öğretimden daha etkili olduğu sonucuna ulaşılmıştır.
Tersine Mühendislik Uygulamalarının Ortaokul Öğrencilerinin Akademik Başarı ve Problem Çözme Becerilerine Etkisi